A productivity dashboard for hospitals: an empirical study - Pestana, M. (2018)
Health information systems are key assets in managing health units’ daily operations. Nevertheless, literature is scarce concerning information systems for increasing and managing hospital productivity. This study aims at filling such gap through an empirical research based on large Portuguese hospital. Specifically, a dashboard prototype is proposed addressing productivity indicators in areas such as assistance, hospitalization, surgery, among others. This dashboard is tuned using a design science research approach where health experts successively validate the prototype. Interviews are conducted to assess the benefits of using our proposal to manage productivity on a daily basis.